The despised body of Paul: Power-somatic conflicts in early pauline communities - Zamora Santiago, Gerson (2024)
This work aims to delve into discussions concerning the relationship between body and power within the early conflicts of Pauline Christianity. Ideals and ideological transmission, particularly pertaining to a somatic classification of power in the most urbanized cities of the Roman Empire in the 1st century, compelled Paul to employ a rhetoric of suffering in order to uphold his somatic (apostolic) legitimacy. Within the symbolism of Roman power, Paul does not embody the hegemonic stereotype of a divine emissary. In this context, the apostle introduces the discourse of the Crucified body, “bearing in the body the death of Jesus everywhere” (2 Cor 2:4). This serves as a response to accusations and ideological discourses that politically disdain bodies, diverging from the ideals of the Greco-Roman elite.